A review on electrospun membranes for potential air filtration application. Issue 5 (October 2022) - Russo, Francesca; Castro-Muñoz, Roberto; Santoro, Sergio; Galiano, Francesco; Figoli, Alberto
Abstract: Air pollution is one of the major environmental concerns in most highly populated cities, which is typically caused by particulate (PM2.5 and PM0.1 ) or gaseous pollutants. In this framework, membranes produced by the electrospinning technique are attracting more and more interest thanks to their peculiar properties such as interconnected pore structure, tunable porosity and fiber dimension, high surface area to volume ratio and controllable morphology. This review aims to provide an exhaustive overview on the electrospun membranes applied in air filtration introducing the key principles and fundamentals of the separation mechanisms and discussing the influence of membrane properties (e.g., morphology and charge) on their filtration efficiency. The materials generally employed for the fabrication of electrospun membranes (polymers, solvents) and their combination with additives with defined properties are reviewed also in light of the new environmentally friendly approaches which are increasingly adopted in membrane fabrication. Finally, the practical use of electrospun membranes in several application fields such as individual protection devices, environmental remediation, recovery of volatile organic compounds (VOCs), and ventilation and climate control aspects is widely discussed providing also an outlook on the upscaling potential of electrospun membranes and future directions. Graphical Abstract: ga1 Highlights: Air filtration mechanisms involved in electrospun membranes are investigated. The polymers, biopolymers, traditional and non-toxic solvents, and additives are analysed. Electrospun membranes for air filtration applications are discussed.